Spatial issues on firm demography: an analysis for Argentina - Calá, Carla Daniela (2009)
Firm turnover (entry, exit and survival) inside manufacturing markets and the determinants of location of new ventures in a specific territory are relapsing subjects in the area of, respectively, Industrial Organization and Regional and Urban Economics. However, from beginnings of the nineties these subjects have recovered protagonism. The availability of better datasets, the advances in the Location Theories and Industrial Dynamics and the use of more sophisticated econometric tools (discrete choice, Poisson, panel data, etc.) help to explain the increasing interest of scholars in these subjects. This thesis project is set inside those perspectives and aims, on the one hand, to review the main theories and determinants that explain firm demography and, on the other hand, to explain the motivation and objectives for future research. The latter approaches some of the critical questions in this literature within the framework of a developing economy (Argentina). Using such empirical application constitutes a clear novelty inside an empirical literature centered in cases as Europe, North America or Japan, while very few empirical contributions do exist regarding countries out of these areas and, concretely, for developing countries.